Efficacy and Safety of Chinese Herbal Medicine for Primary Intracerebral Hemorrhage: A Systematic Review of Randomized Controlled Trials - Wang, Hui-Lin; Zeng, Hua; Xu, Meng-Bei; Zhou, Xiao-Li; Rong, Pei-Qing; Jin, Ting-Yu; Wang, Qi; Zheng, Guo-Qing (Frontiers in Pharmacology, 2019)
Abstract Background: Primary intracerebral hemorrhage (ICH) is the most harmful subtype of stroke, but there have yet been no specific proven therapies. Chinese herbal medicine (CHM) has been used for ICH for more than thousand years; however currently it is still lack of available evidence. The objective of this study is to assess the current available evidence of CHM for acute ICH according to randomized controlled trials. Methods: Eight databases were searched from their inception to November 2017. Only the studies that assessed at least 4 domains with ‘yes’ according to the Cochrane risk of bias tool were selected for analysis. All the data were analyzed by using Review Manager 5.3 software. P<0.05 was considered to be statistically significant. Results: Forty-five studies with 4517 individuals were identified. CHM paratherapy can improve dependency, volume of hematoma, volume of perihematomal edema, clinical effective rate, and neurological function deficit compared CHM alone or placebo (all P<0.05). By contrast, it was not significant for improving mortality rate of ICH patients (p>0.05). In addition, adverse events were reported in 16 studies, whereas 29 studies did not mention it. The frequency of adverse events was 70/972 in the trial group and 48/944 in the control group. Conclusion: The present study provided supportive evidence of CHM for improving dependency of ICH and showed generally safety; however, there is still lack of evidence for improving mortality rate, and it opens for further study.